THE BALANCE OF LEGAL CERTAINTY AND UTILITY IN BALI’S ALCOHOL REGULATION - Santosa, Anak Agung Gede Duwira Hadi; Wijaya, I Made Marta (Universitas Lampung, 2024)
Traditional alcoholic beverages hold a significant place in the culture of Indonesia, embodying the nation's rich heritage and diverse local wisdom. However, the regulation of these beverages presents critical concerns regarding public health and societal impact. This study critically examines how the principles of legal certainty and utility are reflected in Bali Governor Regulation Number 1 of 2020 (“Bali’s Alcohol Regulation”). The primary objective of this research is to analyze and evaluate the embodiment of these values within the regulation. Employing a normative legal research methodology, the study scrutinizes the regulation alongside the hierarchy of laws governing it. The findings reveal notable inconsistencies between Bali’s Alcohol Regulation and the definitions of traditional alcoholic beverages established in higher legislative frameworks, raising pertinent questions about the balance between legal certainty and the practical benefits offered by the regulation. Furthermore, the analysis indicates that the regulation fails to uphold several legal principles, leading to ambiguity in its enforcement. From a utility perspective, the regulation does not yield substantial benefits for artisans, producers, distributors, sellers, buyers, or the broader community. Consequently, it falls short of meeting adequate utility standards, underscoring the necessity for revision and enhancement to better accommodate the interests of all stakeholders involved in the traditional alcoholic beverage sector in Bali.